PROTECTION OF WIFE’S RIGHTS AFTER A CONTESTED DIVORCE (Analysis of Judge's Decision Number: 143/Pdt.G/2014/PA.Sgm) - Efrinaldi, Efrinaldi; Jayusman, Jayusman; Margono, Aris; Putra, Andi Eka; Bunyamin, Mahmudin (Universitas Islam Negeri Raden Intan Lampung, 2024)
The research discusses the considerations of judges at the Sungguminasa Religious Court regarding fulfilling the rights of wives after divorce, decision Number: 143 /Pdt.G/2014/PA.Sgm. It is generally accepted that in contested divorce cases, there are no rights to the wife after the divorce. The judge's decision that was accepted usually only granted the divorce petition. Judges usually did not grant it if there were claims for their rights and the rights of children post-divorce in the lawsuit. This research question is: What is the progressive legal analysis of the judge's considerations in case Number: 143 /Pdt.G/2014/PA.Sgm? This research was a literature study related to the considerations of judges' decisions in case number: 143/Pdt.G/2014/PA.Sgm. The primary data of this research was the decision of case number: 143/Pdt.G/2014/PA.Sgm. The judge's considerations in the decision were analyzed using Progressive Law theory to conclude. After collecting data through interviews, the findings of this research are that the Judge's considerations in Decision Number: 143 /Pdt.G/2014/PA.Sgm in fulfilling the wife's rights after a divorce from her husband, is progressive. The panel of judges granted the wife's civil rights after the divorce based on the defendant's capabilities. This decision benefits and provides financial protection for the ex-wife in continuing her life.